Remembering Augustine: The Architectonic Structure of His Theology of Memoria - Stephenson, Christine Felicidad (2023)
Augustine recognized memory to be pivotal in his journey to know and understand God and in his remembrance of God. His theology of memoria is complex, multi-faceted, and best described in Confessiones X. Architectonics, an investigatory “tool” used to examine Augustinian memory, reveals in greater depth Augustine’s logical, profound, and multi-faceted approach in his interrogation of memory. Architectonics has unveiled four main neoteric discoveries. First, the architectonic structure of memory which elucidates the foundational pillars of memory in Conf. X and his earlier writings. These occur in a particular sequence: location of memoria, power of memory, sense-perception, teaching/learning, recollection and forgetfulness, images, phantasiae and phantasmata, transiency of memory, the beata vita. Second, Arc-hitectonics (Arc) and memory where Arc, a unique memory gene involved in neuronal communications, identifies a potential genomic memory process that provides knowledge regarding the inner workings of memory. Third, architectonics, time, and memory where a model for the simultaneity of the three cardinal “moments” of time - creation, the Incarnation, and eternity, with temporal time - past, present, and future, and physical time illustrated by the Arc gene. Arc in physical time intercalates with eternity and temporal time. Four, the theory of recapitulation where XIII recapitulates I-XII as viewed through creation and other motifs present in Confessiones. The architectonic investigation of Augustinian memory provokes a new way of thinking about memory and Confessiones – a re-thinking of Augustine’s theology of memoria.